Etiologies of Long-Term Postcholecystectomy Symptoms: A Systematic Review - Carmen S. S. Latenstein; Sarah Z. Wennmacker; Judith J. de Jong; Cornelis J. H. M. van Laarhoven; Joost P. H. Drenth; Philip R. de Reuver (Gastroenterology Research and Practice)
Background. Cholecystectomy does not relieve abdominal symptoms in up to 40% of patients. With 700,000 cholecystectomies performed in the US, annually, about 280,000 patients are left with symptoms, making this a serious problem. We performed a systematic review to determine the different etiologies of long-term postcholecystectomy symptoms with the aim to provide guidance for clinicians treating these patients. Methods. A systematic search of the literature was performed using MEDLINE, EMBASE, and Web of Science. Articles describing at least one possible etiology of long-term symptoms after a laparoscopic cholecystectomy were included in this review. Long-term symptoms were defined as abdominal symptoms that were present at least four weeks after cholecystectomy, either persistent or incident. The etiologies of persistent and incident symptoms after LC and the mechanism or hypothesis behind the etiologies are provided. If available, the prevalence of the discussed etiology is provided. Results. The search strategy identified 3320 articles of which 130 articles were included. Etiologies for persistent symptoms were residual and newly formed gallstones (41 studies, prevalence ranged from 0.2 to 23%), coexistent diseases (64 studies, prevalence 1-65%), and psychological distress (13 studies, no prevalence provided). Etiologies for incident symptoms were surgical complications (21 studies, prevalence 1-3%) and physiological changes (39 studies, prevalence 16-58%). Sphincter of Oddi dysfunction (SOD) was reported as an etiology for both persistent and incident symptoms (21 studies, prevalence 3-40%). Conclusion. Long-term postcholecystectomy symptoms vary amongst patients, arise from different etiologies, and require specific diagnostic and treatment strategies. Most symptoms after cholecystectomy seem to be caused by coexistent diseases and physiological changes due to cholecystectomy. The outcome of this research is summarized in a decision tree to give clinical guidance on the treatment of patients with symptoms after cholecystectomy.